2013
DOI: 10.2478/s11756-013-0256-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture variability on a steep slope near a ridge in a forested mountain range, Shikoku, Japan: a model study

Abstract: Variability in soil moisture on a steep slope near a ridge in a forested mountain range, Shikoku, Japan, was studied observationally and numerically. Vertically integrated soil moisture, from a depth of −60 cm to the surface, W, was introduced as a key indicator, and its seasonal variation was analysed on a daily basis from August 2011 to August 2012. The “bucket with a bottom hole” (BBH) model of Teshima et al. (2006) was improved to consider the forest environment in simulating the variation in W. A “big-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These studies are mostly based on a model, which describes a biophysical system. Model simulations are widely used and unique tools for risk assessment, planning of adaptation measures and scenario analyses to assess the combined effects of land use, agricultural practices, and climate change on soil and water quality (Even & Parkin 1996;Hanel et al 2012;Mori et al 2013;Nikodem et al 2013;Jian et al 2014). Process-based models, describing physical processes of the investigated system have the ability to simulate variables under altered future conditions, supposing that the current physical relations remain valid under changing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are mostly based on a model, which describes a biophysical system. Model simulations are widely used and unique tools for risk assessment, planning of adaptation measures and scenario analyses to assess the combined effects of land use, agricultural practices, and climate change on soil and water quality (Even & Parkin 1996;Hanel et al 2012;Mori et al 2013;Nikodem et al 2013;Jian et al 2014). Process-based models, describing physical processes of the investigated system have the ability to simulate variables under altered future conditions, supposing that the current physical relations remain valid under changing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They found that (i) runoff coefficients during the first 7 months following the wildfire were similar for the Pine and the Eucalypt plantation, (ii) observed/inferred annual erosion rates over the first two years following the wildfire were also comparable at the two study sites, (iii) terracing seemed to enhance overland flow generation, and (iv) terracing appeared to increase erosion rates at both study sites by at least one order of magnitude. Mori et al (2013) analysed data on soil water content obtained on a steep slope near a ridge in a forested mountain range in south-western Japan. They constructed a simple prediction model by improving the "bucket with a bottom hole" model, and applied it to experimental data obtained on a forested slope to simulate the dynamics of soil moisture beneath the forest floor.…”
mentioning
confidence: 99%